EFFECTIVENESS OF COMPETENCY-BASED TRAINING PROGRAMS IN ADDRESSING UNEMPLOYMENT AT THE AMUNTAI VOCATIONAL TRAINING CENTER (BLK), NORTH HULU SUNGAI REGENCY - Ratna Sari; Hendrayani; Djayeng Turano Gunade (International Journal of Economic Integration and Regional Competitiveness, 2024)
Objective: A competency-based training program is an activity intended to improve and change attitudes, behavior, skills and knowledge. However, the effectiveness of competency-based training programs is less effective because they are not carried out directly, lack of time for implementation, inadequate facilities and infrastructure. This study aims to determine the effectiveness of competency-based training programs in efforts to overcome unemployment and the factors that influence it. Method: This research method uses descriptive qualitative, with data collection techniques namely interviews, observation and documentation. Then the withdrawal of informants by purposive sampling amounted to 16 people. After the data is collected, it is then analyzed using techniques including data reduction, data presentation, drawing conclusions, and testing the credibility of the data including extending observations, increasing dedication in research, triangulation, using reference language, member check. Results: The results of this study indicate that the effectiveness of competency-based training programs in efforts to tackle unemployment at the Amuntai Vocational Training Center (BLK) in Hulu Sungai Utara District is less effective. This can be seen from: The indicators of socialization of the training program have not been effective. Indicators of the implementation of the training program have not been effective. Indicators of availability of training funds have not been effective. Indicators of the availability of training facilities and infrastructure have not been effective. The quality indicators for alumni training participants have not been effective. Factors influencing the effectiveness of competency-based training programs in efforts to tackle unemployment at the Amuntai Vocational Training Center (BLK) in Hulu Sungai Utara, namely: lack of training funds, limited job training. Novelty: To increase the effectiveness of competency-based training programs in efforts to tackle unemployment, it is suggested to the Amuntai Vocational Training Center (BLK) to carry out training program socialization directly to the community, extend the training program implementation time in each existing department, improve facilities and infrastructure supporting training programs, increasing the discipline of competency-based training participants at the Amuntai Vocational Training Center (BLK).